Competitive effects of resale price maintenance through inventory: Evidence from publishing industry - Kohei Kawaguchi; Yin Jia Qiu; Yi Zhang (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2022)
This paper examines the competitive effects of resale price maintenance (RPM) through inventory decisions under demand uncertainty. We focus on the Japanese publishing industry where RPM is allowed. We develop and estimate a model of RPM in which price and inventory are determined before demand is realized. Counterfactual simulations show that the RPM model would yield a higher consumer surplus than a wholesale model due to a sufficient inventory and a lower price of new titles. Moreover, we show that the price ceiling due to RPM plays a welfare-enhancing role, whereas the price floor is irrelevant in the industry.
Keywords: L11; L13; L42; L81; L82; M31; K21; 330; Resale price maintenance; Return policy; Vertical relationship; Antitrust law; Demand uncertainty; Inventory; Product variety; Publishing industry; Book stores